ANALISIS KINERJA KEUANGAN PT. PERUSAHAAN GAS NEGARA, TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA DITINJAU DARI ASPEK PROFITABILITAS - Maria Assumpta De Araujo; Soni letek; Yohanes Soares (Journal Accounting International Mount Hope, 2024)
Analysis of Financial Performance of PT. Gas Company State, Tbk Listed on the Indonesian Stock Exchange in Review from Profitability Aspects of the Year 2014-2020. The formulation of the problem raised is how the financial performance of the company PT. State Gas Company, Tbk is seen from the profitability aspects. The purpose of this research is to find out how the financial performance of the State Gas Company, which is seen from the profitability aspects. The data used in this research is secondary data, which is a financial report document. The data analysis technique in this study is to use non-statistical analysis techniques to determine the size of the financial ratio. Based on the results of the analysis obtained the conclusion that the financial performance of PT. State Gas Company, Tbk during the year 2014-2020 based on the ratio of profitability assessed. The recommendation that can be given to the researchers is PT. National Gas Company. The management should pay attention mainly to the policies that will be taken mainly in the financial management in order to be able to pay attention to the poor economic performance of the company, and for the users of financial reports with the presence of the calculation of the profitability ratio this is expected to be useful as additional information before taking decisions related to the company.